ISO-22000 – standard dla organizacji w łańcuchu obrotu żywnością - Skowron, Paweł (ISO-22000 – Standard for organizations in the food chain, 2008)
Organizations within the food chain should identify hazards in food at any stage of the food chain with all the parties participating in the food chain. This article presents a new standard in food industry – ISO 22000:2005 – Management of food safety, which helps organizations identify and assess food hazard. The author also shows connections of the HACCP with the requirements of document PN – EN ISO 22000:2006. It should be noted that the standard of food safety consists of six documents, which two of them will be prepared soon. The author of this article pays attention to Polish food companies which have a lot of problems with the rules of Polish and European food law.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 22, s. 204-214